Reconstructing subjects : a philosophical critique of psychotherapy - Shawi, Hakam H. Al- (Value Inquiry Book Series, 2011)
This work is about the deceptive nature of psychotherapy. In particular, it is about those therapies that claim to provide the client with insight and self-knowledge when in practice they are a means of social control absorbing clients into socially acceptable norms. Through a philosophical analysis of key concepts such as knowledge, insight, and subjectivity, and through an examination of mechanisms intrinsic to psychotherapeutic practice, such as power, interpretation, and suggestion, this monograph unveils how psychotherapy deludes clients into believing they have discovered their true self. Rather than gaining self-knowledge and insight into their true or core self, clients are subtly reconstructed and reconfigured along prevailing social values. Furthermore, the very epistemological and metaphysical world-view clients are deceived into believing is highly suspect and founded upon a fascistic understanding of knowledge. As an alternative to such domination, psychotherapy needs to reconstruct itself along Nietzschean-Deleuzian lines where the focus is on multiple identities, difference, and creativity. Rather than focusing on an analysis of past memories to alleviate symptoms such as anxiety or depression, therapeutic intervention should aim for a non-repressive conception of self-knowledge and insight based upon a creative future and not a regretful past. This entails a different understanding of knowledge and reality that is not based on subjugating the world to what we know about it, but on immersing ourselves within reality in all of its concrete richness. And such an approach is preferable not because it is "true" but because it is more liberating.